Effect of Incentives and Job Satisfaction on Performance Employees Through The Spirit of Work at Badan Lingkungan Hidup Sumatera Utara - Chairun Nisa; Prihatin Lumbanraja; R Hamdani Harahap (CV. AFDIFAL MAJU BERKAH, 2022)
Government organizations as a form of public service have the aim of prospering the community through the services provided to the community. Badan Lingkungan Hidup Sumatera Utara is one of the government organizations that carries out regional government affairs in the North Sumatra Province in the environmental field. This agency plays a role in activities related to environmental problems such as pollution, factory waste, garbage, land disputes, and all matters related to environmental issues. . The research was Badan Lingkungan Hidup Sumatera Utara. This type of research is an associative quantitative approach. The number of samples studied in this study were 58 respondents. Data analysis was carried out through PLS-SEM using the SmartPLS program. The results showed that incentives had a positive and insignificant effect on employee performance. Job satisfaction has a positive and insignificant effect on employee performance, work morale has a positive and significant effect on employee performance, incentives have a positive and significant effect on work morale, job satisfaction has a positive and significant effect on work morale, incentives and job satisfaction have a positive and significant effect on performance employees through the spirit of work